Pendampingan Kerohani Islam dalam Meningkatkan Motivasi Keagamaan Wali Murid PAUD Wildani dan SDI Ghilmani di Majlis Ta’limul Qulub LPI AL-HAROMAIN Cabang Blora Dk. Bladeg Ds. Kutukan Kec. Randublatung Kab. Blora - Hidayah , Luthfi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Humans as religious beings, God supplies humans with the pleasure of thinking, feeling confused, anxious and indecisive to learn and understand the natural surroundings as a balance in feelings of doubt and fear. This is what drives people to seek strength that can protect and guide them in Islamic spirituality so that they can become motivation in critical times. Religious encouragement should be fulfilled so that the human person will get a satisfaction and peace of mind. Therefore, in PAUD Wildani and SDI Ghilmani Schools, they facilitate infrastructure in the form of Majlis Ta'lim which aims to deepen religion so that they can become Islamic spiritual companions for the parents of students and the surrounding community.